Association of mindfulness on state-trait anxiety in choking-susceptible athletes: mediating roles of resilience and perceived stress - Tang, Yiwei; Jing, Longjun; Liu, Yang; Wang, Huilin (Frontiers in Psychology, 2023)
Introduction It is a well-documented psychological phenomenon for athletes to experience abnormal performance on the field, often called choking. Negative emotions such as perceived stress and state-trait anxiety have been linked to this phenomenon. In an effort to delve into the intricate relationship between mindfulness and state-trait anxiety among athletes susceptible to choking, this study was conducted in Central China during the period from October to November 2022. Methods The sample selection process employed a combination of cluster sampling and random sampling, resulting in a total of 377 viable samples encompassing choking-susceptible athletes who frequently grapple with state-trait anxiety and demonstrate performance deviations. The data analysis was executed utilizing AMOS v.26. Results The results indicate a negative association between mindfulness and perceived stress (standardized coefficient = −0.224, p < 0.001), resilience and perceived stress (standardized coefficient = −0.237, p < 0.001), as well as perceived stress and state-trait anxiety (standardized coefficient = 0.510, p < 0.001). The positive impact of mindfulness on state-trait anxiety is mediated by resilience and perceived stress (standardized indirect effect = 0.237, p < 0.001). The explanatory power of this study is R2 = 0.35. Discussion Drawing from these substantial findings, a key recommendation is to implement mindfulness training programs for athletes prone to choking. This proactive measure, facilitated by sports departments, clubs, and coaches, could potentially alleviate state-trait anxiety, enhancing athletes’ mental well-being and optimizing their performance outcomes during competitions.